Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood - Frolov, Andrey V.; Montreuil, Olivier; Akhmetova, Lilia A. (Zootaxa, 2016)
The subfamily Orphninae (Coleoptera: Scarabaeidae) is reviewed from Madagascar. A total of four genera and 39 species were found, all being endemic to the island. The following five new species are described: Triodontus ankarafantsikae, Triodontus lemoulti, Triodontus viettei, Triodontus fairmairei, and Triodontus inexpectatus. The following new synonymies are proposed: Orphnus nigrita Brancsik, 1893 is synonym of Triodontus hova (Fairmaire, 1868); Triodontus occidentalis Paulian, 1977 and Orphnus obsoletus Brancsik, 1893 are synonyms of Triodontus nitidulus (Guérin-Méneville, 1844); Triodontus vadoni Paulian, 1977 and Triodontus perrotorum Paulian, 1977 are synonyms of Triodontus owas Westwood, 1852. Lectotypes are designated for the following names: Orphnus nitidulus Guérin-Méneville, 1844 and Orphnidius modestus Benderitter, 1914. Keys, descriptions, illustrations of habitus and male genitalia, and distributional records maps are given for all species.